Cell‐ and region‐specific expression of depression‐related protein p11 (S100a10) in the brain. Issue 4 (21st October 2016) - Milosevic, Ana; Liebmann, Thomas; Knudsen, Margarete; Schintu, Nicoletta; Svenningsson, Per; Greengard, Paul
ABSTRACT: P11 (S100a10), a member of the S100 family of proteins, has widespread distribution in the vertebrate body, including in the brain, where it has a key role in membrane trafficking, vesicle secretion, and endocytosis. Recently, our laboratory has shown that a constitutive knockout of p11 (p11‐KO) in mice results in a depressive‐like phenotype. Furthermore, p11 has been implicated in major depressive disorder (MDD) and in the actions of antidepressants. Since depression affects multiple brain regions, and the role of p11 has only been determined in a few of these areas, a detailed analysis of p11 expression in the brain is warranted. Here we demonstrate that, although widespread in the brain, p11 expression is restricted to distinct regions, and specific neuronal and nonneuronal cell types. Furthermore, we provide comprehensive mapping of p11 expression using in situ hybridization, immunocytochemistry, and whole‐tissue volume imaging. Overall, expression spans multiple brain regions, structures, and cell types, suggesting a complex role of p11 in depression. J. Comp. Neurol. 525:955–975, 2017. © 2016 Wiley Periodicals, Inc. Abstract : P11 is a protein with a key role in depressive‐like behavior and antidepressant action. Here we provide a comprehensive expression data identifying discrete brain regions and specific cell types in which p11 is expressed. We discuss the significance of this pattern of expression in the context of major depressive disorder.